2019
DOI: 10.48550/arxiv.1904.07345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subaru High-z Exploration of Low-Luminosity Quasars (SHELLQs) VIII. A less biased view of the early co-evolution of black holes and host galaxies

Takuma Izumi,
Masafusa Onoue,
Yoshiki Matsuoka
et al.

Abstract: We present ALMA [C II] line and far-infrared (FIR) continuum observations of three z > 6 lowluminosity quasars (M 1450 > −25 mag) discovered by our Subaru Hyper Suprime-Cam (HSC) survey. The [C II] line was detected in all three targets with luminosities of (2.4 − 9.5) × 10 8 L ⊙ , about one order of magnitude smaller than optically luminous (M 1450 < ∼ −25 mag) quasars. The FIR continuum luminosities range from < 9 × 10 10 L ⊙ (3σ limit) to ∼ 2 × 10 12 L ⊙ , indicating a wide range in star formation rates in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 106 publications
1
17
0
Order By: Relevance
“…Based on the CO-based dynamical mass estimates and the SMBH mass taken from the literature (see Table 3; Hao et al 2005), we also investigated the possible constraints of the relationship between the black hole and the host galaxy in IR QSO systems, and found that almost all local IR QSOs in our sample are located on or below the local BH-bulge mass relation (equating M dyn to M bulge ) with mass ratio of M BH /M dyn ranging from 0.02% to 0.36% with a median value of 0.08%, about 3−4 times lower than the local BH to bulge mass ratio at M BH = 10 7 M (Kormendy & Ho 2013). This is similar to IBISCO hard X-ray selected AGN sample galaxies at z < 0.05, most of which are found to show large offsets with BH mass below the local relationship (Feruglio et al 2018), and low-luminosity QSOs at z > 6 as well (Izumi et al 2019). As hypothesized by Xia et al (2012), the low ratio of M BH /M dyn is likely to imply that the star formation and the AGN activities are not necessarily synchronized and the SMBH may grow faster after the short IR QSO phase, even though they are intimately connected.…”
Section: Smbh and Host Galaxy Growthsupporting
confidence: 65%
“…Based on the CO-based dynamical mass estimates and the SMBH mass taken from the literature (see Table 3; Hao et al 2005), we also investigated the possible constraints of the relationship between the black hole and the host galaxy in IR QSO systems, and found that almost all local IR QSOs in our sample are located on or below the local BH-bulge mass relation (equating M dyn to M bulge ) with mass ratio of M BH /M dyn ranging from 0.02% to 0.36% with a median value of 0.08%, about 3−4 times lower than the local BH to bulge mass ratio at M BH = 10 7 M (Kormendy & Ho 2013). This is similar to IBISCO hard X-ray selected AGN sample galaxies at z < 0.05, most of which are found to show large offsets with BH mass below the local relationship (Feruglio et al 2018), and low-luminosity QSOs at z > 6 as well (Izumi et al 2019). As hypothesized by Xia et al (2012), the low ratio of M BH /M dyn is likely to imply that the star formation and the AGN activities are not necessarily synchronized and the SMBH may grow faster after the short IR QSO phase, even though they are intimately connected.…”
Section: Smbh and Host Galaxy Growthsupporting
confidence: 65%
“…J0859+0022, J1152+0055, and J2216-0016 were observed in ALMA Cycle 4 (Izumi et al 2018). J2239+0207 and J1208-0200 were observed in ALMA Cycle 5, and will be presented in a forthcoming paper (Izumi et al 2019).…”
Section: Datamentioning
confidence: 85%
“…The bottom panel shows the atmospheric transmission at Maunakea retrieved from the Gemini Observatory (Lord 1992). The vertical lines indicate the central wavelength of broad emission lines expected from the systemic redshift (Mgii redshift for J1205-0000, and [Cii] redshift from Izumi et al (2018Izumi et al ( , 2019 for the others). In each panel, the noise spectra are shown in grey and the best-fit power-law continuum models are shown in blue.…”
Section: Ly Nvmentioning
confidence: 99%
“…Near-infrared (IR) spectra were obtained for 6 quasars, which revealed that the SHELLQs quasars have a wide range of accretion properties, from sub-Eddington accretion onto a massive (M BH > 10 9 M ⊙ ) black hole to Eddington accretion onto a less massive (M BH < 10 8 M ⊙ ) black hole (Onoue et al 2019). Atacama Large Millimeter / submillimeter Array (ALMA) observations were conducted toward 7 quasars, and we found that the host galaxies are forming stars at a rate below that of luminous quasar hosts (e.g., Decarli et al 2018), and that the lowluminosity quasars are more or less on the local relation between black hole mass and host mass (Izumi et al 2018(Izumi et al , 2019. We are also exploiting archival Wide-field Infrared Survey Explorer data to look for red quasars in the SHELLQs sample, which may represent a younger phase of evolution than normal quasars (N. Kato et al, in prep.…”
Section: Introductionmentioning
confidence: 84%